Removing oil spill from water by ferrofluid - Akbal, Can (Open Schools Journal for Open Science, 2021)
Oil spill is a type of environmental pollution caused by the release of liquid petroleum hydrocarbons into the environment due to human activity, especially in the seas. Unfortunately, oil spills are increasing every day in the world’s oceans. Also, the enormous task of cleaning up oil spills in oceans and seas has been burdening industry, government, and environmentalists for decades. In order to find a solution to this significant environmental threat 11th grade student has started a project to remove oil spills from water. With the help of ferrofluids and strong magnets separating the most common types of oils in the oceans: sunflower oil and olive oil is aimed. Due to increasing Covid-19 cases research is completed, and experiment is conducted at home under the guidance of an instructor. According to his experiments and analyzes at home on both types of oils approximately 66% of oil is removed from the water.